IMPACT OF TIME-TO-TREATMENT AND THROMBECTOMY TECHNIQUE ON OUTCOMES IN ACUTE ISCHEMIC STROKE: A SINGLE-CENTER COHORT ANALYSIS - Janevski, Petar; Daskalov, Dejan; Nikolova, Sonja; Aliji, Vjolca; Veljanovski, Dimitar; Arsovska, Anita; Vasilevska, Natasa; Avramoska, Marija Mileska; Jukjic, Edis (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction:  Mechanical thrombectomy (MT) is the standard of care for acute ischemic stroke (AIS) secondary to large vessel occlusion (LVO). Time-to-reperfusion is the most critical determinant of patient outcome. This study aimed to conduct a comprehensive analysis of key time metrics and the efficacy of MT at our institution, evaluating their impact on both angiographic and clinical results to identify areas for process optimization.  Methods:  We conducted a retrospective analysis of a cohort of 17 consecutive patients treated with MT for LVO stroke. We analyzed demographics, baseline clinical status (mRS), occlusion location, detailed time-to-treatment intervals, procedural techniques, and outcomes. The primary angiographic endpoint was successful reperfusion, defined as an extended Thrombolysis in Cerebral Infarction (eTICI) score of 2b or greater. Clinical endpoints included functional outcome at 3 months, measured by the mRS, and the rate of symptomatic intracranial hemorrhage (sICH).  Results:  The mean patient age was 60.9 years, with a significant male predominance (70.6%). All patients presented with severe stroke (initial mRS 4-5), indicating a high-acuity cohort. The mean time from symptom onset to final reperfusion was prolonged at 505 minutes (8 hours 25 minutes). Despite this, a high rate of successful reperfusion (eTICI 2b or greater) was achieved in 85.7% of patients, with complete reperfusion (eTICI 2c or 3) in 57.1%. However, this technical success did not fully translate to clinical recovery, as a good functional outcome (mRS 0-2) at 3 months was achieved in only 30.8% of patients. The rate of sICH was 15.4%.  Conclusion:  Our center achieves high rates of technical success in reperfusion (85.7% eTICI 2b or greater), comparable to international benchmarks. However, prolonged treatment delays are significantly attenuating clinical outcomes, with only 30.8% of patients achieving functional independence. This analysis underscores that procedural excellence alone is insufficient; optimizing system-wide time-to-treatment protocols is the critical next step to improve patient recovery. Keywords: NAT, blood safety, transfusion-transmissible infections, residual risk.